Integration Petrophysical To Identify Reservoir Characterization Of Baturaja Limestone In “X” Well, North West Java Basin - Citra Wahyuningrum; Kevin Kevin; Assyeh Annassrul Majid (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Petrophysical evaluation of the Baturaja Formation on limestone reservoirs of the Field X, using conventional well log interpretation techniques and relating the results to core data based on laboratory analysis, shows that the reservoir characterization parameters to decide future plan for the well. This study shows the role of integrated petrophysical analysis it is possible that an acceptable and can be completed within the constraints and limitations of the available data, but sometimes additional data are needed. These new data, typically additional SCAL (Special Core Analysis), RCAL (Routine Core Analysis), well test data and mud loging data it’s must be integrated. The results of research based on petrophysical parameters is baturaja formation are dominated by limestone. Based on the results of the analysis, the reservoir layer in the baturaja formation, the BRF-1 is a potential hydrocarbon zone while the BRF- 2 and BRF-3 are non-potential zones. The BRF-1 has an average shale volume is 0,187 which is classified as clean formation, a porosity is 0,134 which is classified as small and for a water saturation is 0,677. The calculation method used is the Archie method because it excels in clean formation. Meanwhile, the Simandoux method has advantages in shaly sand formation and the Indonesian method is suitable for formations in Indonesian regions where the dominant formations are shaly sand and low salinity water. Then, cuf-off for BRF-1 obtained a net reservoir of 25.9 m and a netpay of 3,4 m. The results of this data are used to obtain the initial hydrocarbon reserves using the volumetric method and the amount reserves are 84740.5 STB in the BRF-1 zone.